The cardinality of endomorphisms of some oriented paths: an algorithm - Arworn, Sr. (2007)
An endomorphism of a (oriented) graph is a mapping on the vertex set preserving (arcs) edges. In this paper we provide an algorithm to determine the cardinalities of endomorphism monoids of some ( nite) directed paths, based on results on simple paths.